Resilience against brute force and rainbow table attacks using strong ICMetrics session key pairs - Tahir, R.; Huosheng Hu; Dongbing Gu; McDonald-Maier, K.; Howells, G. (2013 1st International Conference on Communications, Signal Processing and Their Applications, 2013)
Cryptography has become an essential for providing security in embedded system applications. The employed cryptographic primitives should provide strong protection such that the security of the system is not compromised at any point in the lifecycle of a secure operation. This particularly includes the secure generation and maintenance of cryptographic keys. In general this assumption is difficult to accomplish, since there are attacks that come under this umbrella ranging from brute force attacks on the key to capturing the node to extract the key. In this paper we investigate and analyze ICMetrics and its counterpart scheme referred to as the scheme for the generation of strong high entropy ICMetrics session key pairs. ICMetrics is a key technology that computes the secret key based on hardware/ software properties of a device, thereby providing resilience against node capture attacks, while high entropy key pair generation scheme is employed to strengthen the generated ICMetrics basis number, so as to safeguard the generated strong key pairs from brute force and rainbow table attacks.